2015
DOI: 10.1007/s00540-015-1982-3
|View full text |Cite
|
Sign up to set email alerts
|

Muscle relaxant effects on insertion efficacy of the laryngeal mask ProSeal® in anesthetized patients: a prospective randomized controlled trial

Abstract: Muscle relaxation appears to facilitate ProSeal insertion efficacy by enabling higher successful insertion rates, higher sealing pressure, lower leakage volume, and lower subjective difficulty of insertion in anesthetized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…We routinely insert cLMA with the aid of muscle relaxants to reduce deep anesthesia-related side effects and possible injuries to patients, although we do not have clear evidence, which might be different from the clinical practice in other institute or country where muscle relaxants are not used for LMA insertion. Muscle relaxants may affect the difficulty level of LMA insertion [24], but it does not affect our conclusions because both groups of patients in our study received muscle relaxants before cLMA insertion. Our patients kept breathing spontaneously during surgery, so results may be less applicable to patients who are paralyzed by muscle relaxants.…”
Section: Discussionmentioning
confidence: 94%
“…We routinely insert cLMA with the aid of muscle relaxants to reduce deep anesthesia-related side effects and possible injuries to patients, although we do not have clear evidence, which might be different from the clinical practice in other institute or country where muscle relaxants are not used for LMA insertion. Muscle relaxants may affect the difficulty level of LMA insertion [24], but it does not affect our conclusions because both groups of patients in our study received muscle relaxants before cLMA insertion. Our patients kept breathing spontaneously during surgery, so results may be less applicable to patients who are paralyzed by muscle relaxants.…”
Section: Discussionmentioning
confidence: 94%
“…After loss of consciousness, mask ventilation was performed using 3-5% sevoflurane in oxygen. 14 Cricoid pressure was applied at a standardized force of 30 N, 5 8 which sufficiently prevents regurgitation into the pharynx, even in patients with a full stomach undergoing Caesarean section. 15 An independent anaesthetist was trained to apply the force by practising on a weighing scale with a top board; within an error of 5%.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Fujiwara et al reported that success rate in first attempt with i-gel was 100%, however, success rate in first attempt with LMA was 84%. 20 Similarly, Acharya et al reported that ease of insertion is higher in i-gel TM as compared LMA classic TM (p<0.05). 21 In the current study, among all patients in i-gel group, insertion time was found to be lower (9.5sec±0.7SD) as compared to patients in LMA group (10.67sec±1.6SD) (p=0.02).…”
Section: Discussionmentioning
confidence: 93%